6-latek jako pierwszoklasista w szkole. Zróżnicowanie kodów językowych dziecka, rodziny i szkoły – dla kogo szansa, dla kogo zagrożenie? - Matejczuk, Joanna; Nowotnik, Anna; Rękosiewicz, Małgorzata (Wydawnictwo Naukowe UAM, 2013)
The article offers another view in the discourse concerning the lowering of school age. We take into consideration the consequences of children’s diversity in terms of the language functioning for their needs, opportunities, and ways to deal with school reality. Our analysis is based on Basil Bernstein’s concept of linguistic codes (1980a and 1980b). Such an interpretation of the phenomenon aims to help to identify the role of the school’s effi ciency of language codes management targeted at six-year-olds. Our aim is to identify the key challenges and tasks facing the school in dealing with the admission and teaching of children with diverse linguistic skills.
Six-year-olds in the fi rst grade of elementary school. A diversity of language codes of the child, family and school – an opportunity or a risk?
Keywords: child-school goodness of fit; early school education; readiness for school; language code; orientation to person and to program; system of communication